The effectiveness of the modified Epley maneuver for the treatment of posterior semicircular canal benign paroxysmal positional vertigo - Chen, Xiaosu; Mao, Jiesheng; Ye, Hua; Fan, Luping; Tong, Qiaowen; Zhang, Hehui; Wu, Chengcheng; Yang, Xiaokai (Frontiers in Neurology, 2023)
Objective: To compare the repositioning effect of the modified Epley maneuver and the traditional Epley maneuver for posterior semicircular canal benign paroxysmal positional vertigo (PC-BPPV). Methods: Sixty-five patients with unilateral PC-BPPV were randomly divided into two groups. The control group received the traditional Epley maneuver, while the experimental group received the modified Epley maneuver, which prolonged the time in the healthy side lying position and the final bowing position. The number of successful repositions after one, two, and three attempts and the total number of successful repositions were recorded and compared between the two groups. A BPPV virtual simulation model was used to analyze the mechanism of the modified Epley maneuver. Results: The first repositioning success rate of the experimental group was significantly higher than that of the control group (85% vs 63%, p=0.040). The experimental group achieved 100% repositioning success rate after two attempts, while the control group needed three attempts to reach 86% repositioning success rate. Four cases in the control group experienced canal switching during the repositioning process, while none in the experimental group did. The BPPV virtual simulation model showed that the modified Epley maneuver could facilitate the passage of otoliths through the posterior arm of the posterior semicircular canal，especially through the location of obstruction. Conclusion: The modified Epley maneuver is more effective than the traditional Epley maneuver in improving the single repositioning success rate and reducing the canal switching rate for PC-BPPV. This study provides a new option for the treatment of BPPV.